2021
DOI: 10.3389/fcell.2021.618102
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Bioactive Plasmalogens in Lung Surfactant

Abstract: Neonatal respiratory distress syndrome (NRDS) is a type of newborn disorder caused by the deficiency or late appearance of lung surfactant, a mixture of lipids and proteins. Studies have shown that lung surfactant replacement therapy could effectively reduce the morbidity and mortality of NRDS, and the therapeutic effect of animal-derived surfactant preparation, although with its limitations, performs much better than that of protein-free synthetic ones. Plasmalogens are a type of ether phospholipids present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 107 publications
0
15
0
Order By: Relevance
“…Interestingly, the alveolar macrophages do not kill in vitro the pathogens unless the latter have been incubated with alveolar lining material (i.e., lung surfactant) before their phagocytosis. Although plasmalogens in lung surfactant are not the major components of the phospholipid mixture, they have been reported to significantly reduce surface viscosity and surface tension (Rüdiger et al, 1998(Rüdiger et al, , 2005Zhuo et al, 2021). The role of plasmalogens in facilitating membrane fusion has been well recognized (Marrink and Mark, 2004).…”
Section: Plasmalogens In Lung Surfactant and Antiviral Pulmonary Surfmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the alveolar macrophages do not kill in vitro the pathogens unless the latter have been incubated with alveolar lining material (i.e., lung surfactant) before their phagocytosis. Although plasmalogens in lung surfactant are not the major components of the phospholipid mixture, they have been reported to significantly reduce surface viscosity and surface tension (Rüdiger et al, 1998(Rüdiger et al, , 2005Zhuo et al, 2021). The role of plasmalogens in facilitating membrane fusion has been well recognized (Marrink and Mark, 2004).…”
Section: Plasmalogens In Lung Surfactant and Antiviral Pulmonary Surfmentioning
confidence: 99%
“…This ether phospholipid, together with cholesterol and surfactant-associated proteins, regulate the surfactant monolayer stability and viscosity. Another key feature is that plasmalogens act as antioxidants and protect alveolar cells from oxidative stress that often encountered at alveolar surface (Zhuo et al, 2021). Plasmalogens may contribute to substantial lowering the surface tension (Rüdiger et al, 1998) and viscosity (Rüdiger et al, 2005) of the lipid mixture.…”
Section: Plasmalogens In Lung Surfactant and Antiviral Pulmonary Surfmentioning
confidence: 99%
“…Figure 1 summarizes a variety of proposed biological functions for plasmalogens as antioxidants in addition to their modulatory role in membrane structure and dynamics ( Bozelli et al, 2021 ). The high susceptibility of the vinyl-ether bond at sn-1 position to radicals including reactive oxygen species (ROS) and reactive nitrogen species (RNS) as well as to the traces of acids supports their important role as a first-line defense system in biology against oxidative damages ( Zhuo et al, 2021 ; Bozelli et al, 2021 ). Previously, Deng and colleagues have proposed that plasmalogens carrying PUFA chains may promote intracellular cubic membranes (CM) formation ( Deng et al, 2009 ) with the implication in virus-induced host CM formation ( Deng et al, 2010 ; Deng and Angelova, 2021 ).…”
Section: Significance Of Plasmalogens As Bioactive Vinyl-ether Lipidsmentioning
confidence: 99%
“…It has been reported that plasmalogens are highly concentrated in lipid bilayer microdomains in cellular and subcellular organelle membranes ( Messias et al, 2018 ). They naturally participate in multiple cellular processes including membrane fusion ( Zhuo et al, 2021 ), cholesterol homeostasis ( Honsho et al, 2015 ), ion transport ( Messias et al, 2018 ) and immunomodulation ( Deng and Angelova, 2021 ). In lipid biosynthesis, plasmalogens can be the source of supply for the precursor of PAF ( Dorninger et al, 2020 ) ( Figure 1 ).…”
Section: Significance Of Plasmalogens As Bioactive Vinyl-ether Lipidsmentioning
confidence: 99%
See 1 more Smart Citation